Teamwork cross-culturally Christ-centered solutions for leading multinational teams - Lingenfelter, Sherwood G.; Green, Julie A. (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2022)
"Intercultural ministry leaders cast a vision for how teams made up of diverse peoples can serve in unity as the body of Christ despite the complicated problems that arise, doing the work of ministry around the world in ways that honor God"--
Includes bibliographical references and index
Keywords: Missions -- Theory; Christian Leadership; Christianity and culture; Multinational work teams